EMBRYO TRANSFER IPSILATERAL AND CONTRALATERAL TO THE POSITION OF THE CORPUS LUTEUM AND EMBRYO SURVIVAL IN LLAMAS - Carnero S., Sylvia (2011)
The study was carried out to evaluate the effect the embryo transfer to the uterinehorn ipsilateral and contralateral to the side of the corpus luteum (CL) and the size of CLon the embryo survival in llamas. It was used 43 recipient adult females randomly assignedto 4 groups: G1 (n=10): CL in right ovary and ipsilateral embryo transfer, G2 (n=10): CL inright ovary and contralateral transfer, G3 (n=15): CL in left ovary and ipsilateral transfer,and G4 (n=8): CL in left ovary and contralateral transfer. Ten llamas were used as embryodonors. They were synchronized with LH (1 ml) on Day 0 (D0), superovulated with 1000UI eCG on D3, luteolysis was induced with PGF2?on D7, and mated on D8. Recipientswere treated on D7 with LH to get synchrony with the donors. On D14 embryos werecollected, evaluated and transferred. The results showed that 60 (G1) and 75% (G3)recipients conceived when embryo transfer was right and left ipsilateral respectively,while only 30 (G2) and 25% (G4) conceived when embryo transfer was right and leftcontralateral respectively. However, statistical difference was only observed between G3with G2 and G4 (p<0.05). These results indicate that pregnancy rate is higher in llamaswhen the embryo transfer was done in to the uterine horn ipsilateral to the CL in the leftovary.